2018
DOI: 10.3389/fgene.2018.00415
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Chicken IRF7 Increased Viral Replication and Programmed Cell Death to the Avian Influenza Virus Infection Through TGF-Beta/FoxO Signaling Axis in DF-1

Abstract: During mammalian viral infections, interferon regulatory factor 7 (IRF7) partners with IRF3 to regulate the type I interferon response. In chickens, however, it is still unclear how IRF7 functions in the host innate immune response, especially given that IRF3 is absent. To further elucidate the functional role of chicken IRF7 during avian influenza virus (AIV) infection, we generated inducible IRF7 overexpression DF-1 cell lines and performed in vitro infection using low pathogenic AIVs (LPAIVs). Overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 60 publications
2
24
0
Order By: Relevance
“…In our previous studies, we consistently observed a significant upregulation of IFNB expression as a result of IRF7 overexpression in the DF-1 cell lines upon dsRNA induction or H6N2 infection [14,35]. On the other hand, IFNA mRNA levels were not significantly affected by the level of IRF7 expression [14,35], and a similar pattern was observed in this study ( Figure 1E-G). Although DF-1 cells are capable of mounting a type I IFN response, the level of response is possibly lower than that of primary CEFs due to a higher suppressor of cytokine signaling 1 (SOCS1) expression in DF-1 [42].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In our previous studies, we consistently observed a significant upregulation of IFNB expression as a result of IRF7 overexpression in the DF-1 cell lines upon dsRNA induction or H6N2 infection [14,35]. On the other hand, IFNA mRNA levels were not significantly affected by the level of IRF7 expression [14,35], and a similar pattern was observed in this study ( Figure 1E-G). Although DF-1 cells are capable of mounting a type I IFN response, the level of response is possibly lower than that of primary CEFs due to a higher suppressor of cytokine signaling 1 (SOCS1) expression in DF-1 [42].…”
Section: Discussionsupporting
confidence: 90%
“…The type I IFN induction models from in vitro studies using mouse embryonic fibroblast or primary tracheal epithelial cells of Irf7 -/mice showed an abolished production of type I IFNs upon viral infection [10,41]. In our previous studies, we consistently observed a significant upregulation of IFNB expression as a result of IRF7 overexpression in the DF-1 cell lines upon dsRNA induction or H6N2 infection [14,35]. On the other hand, IFNA mRNA levels were not significantly affected by the level of IRF7 expression [14,35], and a similar pattern was observed in this study ( Figure 1E-G).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations